2020
DOI: 10.35848/1882-0786/abb642
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic shield integration for a chip-scale atomic clock

Abstract: We introduce a miniaturized magnetic shield integrated into the physics package of a chip-scale atomic clock. The primary shield, which is formed by a stack of precision-machined high-permeability plates, compactly sits inside the package as it is designed to be the internal supporting frame. Further improved by a Kovar lid, the best frequency sensitivity to a longitudinal external field is 1.1(3) × 10−11/μT, which is consistent with the measured shielding factor, while the transverse sensitivity is well below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Our chip-scale magnetometer package is basically identical to the one we used for a compact CPT clock [ 28 ]. The core spectroscopy unit is comprised of a vertical cavity surface emission laser (VCSEL), a quarter wave plate (QWP), a micro-fabricated cesium vapor cell, and a photodiode all aligned vertically ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our chip-scale magnetometer package is basically identical to the one we used for a compact CPT clock [ 28 ]. The core spectroscopy unit is comprised of a vertical cavity surface emission laser (VCSEL), a quarter wave plate (QWP), a micro-fabricated cesium vapor cell, and a photodiode all aligned vertically ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The board distributes signals to off-the-shelf instruments for measurement and control ( Figure 3 d). We employ a compact magnetic shield, which allows us easy characterization of the package [ 28 ]. Although imperfect, it could be used, after nulling, for providing a zero-field environment due to small field-inhomogeneity as revealed in the linewidths of CPT spectra for high ’s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 For atomic magnetometers or atomic clocks, only the alkali metal atoms need to be polarized, thus few hundreds of µW pump power is usually enough. [20][21][22] However, when there are noble gas atoms which require to be hyper-polarized, many research indicated that 1 mW pump power is generally not sufficient. [23][24][25][26] This causes great challenges to the development of compact atomic gyroscopes.…”
Section: Introductionmentioning
confidence: 99%
“…There are various applications of on chip light–atom interactions, such as chip‐scale magnetometer, [ 1–3 ] frequency reference, [ 4 ] atomic clock, [ 5–8 ] quantum logic gate, [ 9–11 ] single‐photon switch, [ 12 ] and quantum repeater, [ 13–15 ] realized by local field enhancement and light modulation. For example, an on‐chip atomic magnetometer using special nanostructures has attained a magnetic field measurement precision of 700 pT ( Hz ) 1 , which has tremendous scope for futher improvement while the interaction volume is only 30 μ m × 3.2 μ m × 3.2 μ m .…”
Section: Introductionmentioning
confidence: 99%